(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Antinuclear antibody (ANA) is useful in the diagnosis of systemic lupus erythematosus (SLE). Association of specific autoantibodies with the immunofluorescence pattern of ANA in SLE as noted in Western literature has been taken as reference in all over the world. However, in Bangladesh such research work or data correlating the autoantibodies and their ANA patterns is inadequate. Objective: To identify an association between immunofluorescence patterns of antinuclear antibody on HEp-2 cell and more specific antinuclear reactivities (e.g. anti-dsDNA and anti-extractable nuclear antigen) in the serum samples of SLE patients. Methods: Serum samples of 37 SLE patients who were diagnosed by ARA (American Rheumatism Association) classification criteria and laboratory tests, attending at lupus clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU) during the study period of six months were subjected for ANA testing by Indirect Imrnunofluorescence (IIF) on HEp-2 cell, anti-dsDNA by ELISA and anti- extractable nuclear antigen (anti-ENA) by Dot Immunoblot. Dot blot strips were tested for anti-Sm, anti-RNP, anti-SSA/Ro, and anti-SSB/La. Results: Out of 37 SLE patients 32 (86.5%) cases were ANA positive by IIF on HEp-2 cell. ANA positive sera exhibited three fluorescence patterns such as speckled (43.7%), peripheral (34.3%) and homogenous pattern (21.8%). Peripheral pattern (100%) was strongly associated with anti-dsDNA (p<0.05) and homogenous pattern (85.7%) was also predominantly associated with anti-dsDNA (p<0.05). Speckled pattern (85.6%) was significantly associated with anti-ENA (p<0.05). Anti-dsDNA was positive in 75% of SLE cases and majority (45.8%) of which showed peripheral pattern whereas anti-ENA was positive in 48.6% cases and majority (70.5%) of which showed speckled pattern. The most commonly identified antinuclear autoreactivity was directed towards anti-RNP (22.2%) then anti-Sm (16.6%), anti-SSA (16.6%) and anti-SSB (11.1 %). Multiple anti-ENA reactivities were identified in 33.3% cases. Conclusion: Peripheral and homogenous pattern is strongly associated with anti-dsDNA therefore may be predicted that patients have active SLE and speckled pattern may predict anti-ENA (specially ribonucleoprotiens). Thus, ANA-IIF method may suffice and probably reduce the expense of detailed immunological work-up with minimal loss in diagnostic accuracy.